Does time heal all wounds? How is children’s exposure to intimate partner violence related to their current internalizing symptoms? - Ronzón-Tirado, Román; Redondo, Natalia; Zamarrón, María D.; Muñoz Rivas, Marina J. (Frontiers in Psychology, 2022)
The effects of time and longitudinal course of the children’s internalizing symptoms following Intimate Partner Violence Exposure (IPVE) are still of great interest today. This study aimed to analyze the effect of the frequency of IPVE, adverse experiences after the cessation of the IPVE and the time elapsed since the termination of the violent relation on the prevalence of anxiety and depression among children. Participants were 107 children and their mothers who had been victims of IPV and had existing judicial protection and restraining orders. Hierarchical logistic regression models were estimated to analyze children’s adjustment, considering the effect of the time elapsed since the termination, frequency of IPVE, experiences of revictimization, maternal pathology and anxious anticipation of the mother at the prospect of future harm. Exposure to multiple events of violence at the hands of multiple ex-partners and higher scores in the mother’s anxious anticipation were significant predictors of children´s pathological depression and anxiety. Our results emphasize the need for early psychological evaluation of women and children’s victims of IPV to provide timely interventions that avoid symptoms becoming chronic. Strategies to bring support and emotional security to the victims after the end of the violent relationship are desirable.